2020
DOI: 10.1186/s13018-020-01937-7
|View full text |Cite
|
Sign up to set email alerts
|

A CT study of the femoral and sciatic nerve periacetabular moving in different hip positions

Abstract: Background Femoral and sciatic nerves could be damaged during various stages of the periacetabular osteotomy. Changing the position of the hip could be the most effective way of preventing nerve injuries. The purpose of the present study was to investigate the distances of the nerves to various bony landmarks with different hip positions in computerized pelvic scanograms of healthy adults. Materials and methods Fifteen healthy male adults (30 hips) (age 30 ± 6) were included. Scans were performed at three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Isin et al performed a computed tomography (CT) study to examine the distance from the sciatic nerve to the middle of the femoral head and lower border of the triradiate cartilage in varying hip positions. 8 They found that hip flexion decreased the distance from the sciatic nerve to the lower edge of the triradiate cartilage but not the center of the femoral head. However, they pointed out that cadaver studies would be needed to more confidently evaluate the position of the nerve during various hip positions due to difficulty in assessing soft tissue structures on CT.…”
Section: Discussionmentioning
confidence: 97%
“…Isin et al performed a computed tomography (CT) study to examine the distance from the sciatic nerve to the middle of the femoral head and lower border of the triradiate cartilage in varying hip positions. 8 They found that hip flexion decreased the distance from the sciatic nerve to the lower edge of the triradiate cartilage but not the center of the femoral head. However, they pointed out that cadaver studies would be needed to more confidently evaluate the position of the nerve during various hip positions due to difficulty in assessing soft tissue structures on CT.…”
Section: Discussionmentioning
confidence: 97%
“…The degree of recovery after sciatic nerve injury was not related to sex, age, cause of injury, type of fracture, dislocation of the hip joint, or injury to the femoral head (P>0.05). However, patients in whom the injured nerve showed partial recovery had a signi cantly longer mean recovery time (13.78 months [range, 6-23] vs 6.70 months [range, [3][4][5][6][7][8][9][10][11][12]; P<0.05) (Table 7).…”
Section: Partial Recovery Vs Complete Recovery After Sciatic Nerve In...mentioning
confidence: 99%
“…It is the motor nerve of the hamstrings and calf and foot muscles and is an important sensory nerve of the calf and foot. The sensory and motor functions of almost all areas below the knee are innervated by the sciatic nerve [6,7] . This nerve is highly susceptible to injury as a result of displaced acetabular fracture or a dislocated femoral head.…”
mentioning
confidence: 99%
“…It is the motor nerve of the hamstrings and calf and foot muscles and is an important sensory nerve of the calf and foot. The sensory and motor functions of almost all areas below the knee are innervated by the sciatic nerve [7,8]. This nerve is highly susceptible to injury as a result of displaced acetabular fracture or a dislocated femoral head.…”
Section: Introductionmentioning
confidence: 99%